A IMPORTÂNCIA DA FAMÍLIA JUNTO À ESCOLA NO APRENDIZADO FORMAL DAS CRIANÇAS - Josiane Aparecida de Araújo Firman; Sylvia Caroline Russi Santana; Marcos Lupércio Ramos (Universidade do Oeste Paulista, 2015)
The present study aimed to analyze the role of the family in regard to the learning of children in the school environment to occur in their physical, cognitive and social development. It is also intended to analyze and point out the benefits of family intervention in the education of their children and the preposition of some actions to strengthen this relationship and after contribute to the integral formation of children. Through this research can be seen that the family- union school becomes essential for the proper development of the child in their school life and generates enrichment in the teaching learning since both have the same goal, for it is through good school performance of children that favors the acquisition of knowledge that provide skills and skills for citizenship